Flash Card Sebagai Alat Permainan Edukatif untuk Pengenalan Moda Transportasi Perkeretaapian Pada Anak Usia Prasekolah - Apriliani, Nurul Fitria; Puspitasari, Armyta; Prihatanto, Rusman; Aghastya, Adya; Leliana, Arinda (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2025)
Railway technology is increasingly developing and the railway mode is quite a lot of interest by the public with its various advantages making trains an interesting topic for learning materials. Railway safety also needs to be introduced to the community early on. Therefore, socialization related to railway modes and railway safety was carried out to preschool students, namely PAUD “Kasih Ibu” Madiun city students. In addition to introducing railway transportation, this socialization activity also supports the achievement of Learning Outcomes in PAUD, namely the basics of literacy, mathematics, science, technology, engineering and art. The material was delivered with flashcards containing pictures and words about railroad facilities, railroad infrastructure, crew of railroad facilities and railroad safety signs. The evaluation of the activity showed that the average understanding of the socialization participants of the material presented was 80%.